Records Management at PT. Bank Sulselbar Jeneponto Branch - Risma Niswaty; Muh Amin; haedar Akib; Jamaluddin Jamaluddin (Universitas Negeri Makassar, 2020)
Records management plays an important role in the running of an organization. This study aims to determine the description of archival management at PT. Bank Sulselbar Jeneponto Branch. To achieve this goal, the Researcher determined 3 (three) informants, namely: Operations Section Leader, Operational Assistant, and Administrative Assistant. This type of research and the approach used is descriptive qualitative. Collecting data through interview techniques, observation, and documentation. Data analysis techniques are carried out through data collection, data condensation, data presentation, data verification/conclusions. The results showed that archival management at PT. Bank Sulselbar Jeneponto Branch has been managed optimally. This can be seen from the indicators of the stages of receiving archives, the stages of archive storage, the stages of maintaining and securing archives, the stages of shrinking archives, and the stages of destroying archives that have fulfilled almost all aspects of the five stages. Evidenced by the management of records at PT. Bank Sulselbar Jeneponto Branch is adjusted to Standard Operating Procedures and archives that are easy to find as well as an archival storage system using a number system.